Artificial live rock as potential artificial reef toward marine habitat restoration - Muhammad Hamizan bin Yusof (Kulliyyah of Science, International Islamic University Malaysia, 2017)
Over-exploitation on natural live rock exacerbate the degradation of the ocean ecosystem. This concern has been raised since harvesting may reduce the density of marine ornamentals and degrade marine habitat quality. This study aimed to develop artificial live rocks (ALR) that potentially to be used as one of the alternatives toward natural live rocks usage to reduce these over exploitation activities. The study was conducted at Bidong Island, Terengganu started from October 2014 to August 2015. Prior to the study, the mineral analysis was performed to determine the mineral composition of live rock. The result showed that the structure of live rocks consisted of aragonite, calcite, quartz, halite, magnesite, stishovite, illite, rutile, spurrite, sodium chloride and microcline. A total of 100 pieces of ALRs were deployed in October 2014 and retrieved after 2, 4, 6, 8 and 10 months of deployment. Identification in terms of coral spat species and epibenthic organisms was done after the retrieval. 4 species of coral juveniles (Pocillopora sp. and Acropora sp.) and 11 phyla of epibenthic organisms were found attached on ALR. In this study, the retrieved ALR were also used to examine the ability of ALR to act as a biological filter for a marine aquarium. The study positively proved that the ALR was capable of reducing 12 – 51% of nutrient concentration (ammonia, nitrate, nitrite and phosphate) in the marine aquarium. Based on statistical analysis (Two-way ANOVA), there was no significant difference between ALR and natural live rock (p > 0.05) in term of nutrient reduction. PCR- assay was done in order to detect the present of target genes in the ALR. The target genes of nitrifying bacteria and denitrifying bacteria were successfully detected from the ALR samples. It indicated that the ALR might able to retain these bacteria. Based on BLAST result, the samples was closely related to Nitrosomonas sp. and Nitrosospira sp. for nitrifying bacteria and Paracoccus denitrificans and Pseudomonas sp. for denitrifying bacteria. The presence of these bacteria might contribute in reducing the excess nutrient in the marine aquarium. This finding might prove the ability of ALR to be used as substitution for natural live rock and has huge potential to be upgraded as artificial reef towards marine habitat restoration.